Exploring inclusive personas for sustainable UX design - Felfly, Ingrid; Macdow-York, Danielle; Santos, Angeline (My University, 2024)
We wanted to explore how Social Sustainability could be incorporated in User Research in the UX Design field. For this, we chose to dive deeper into what inclusivity could look like in "Personas". When personas have a user base, *inclusive personas* look at the commonly unique needs of users in that user base, so that as much as possible, no one is left out. In the process, we used the Categories of Inclusion (Cognitive Differences, Ethnic backgrounds, Physical Capacity, etc.), the Pyramid of Diversity (ranging from No Difficulties to Severe Difficulties), as well as the Persona Spectrum of Scenarios (Permanent, Temporary and Situational) for inspiration. Some of the challenges encountered were: time, research methods, information architecture and visualization, as well as accessibility to user tests. This was a great opportunity for us and it definitely felt like a starting point that opened up more doors about what inclusion could look like in user research in UX Design, and what level of granularity is useful at that stage so that we can make products more accessible to users.
Presented on April 19, 2024 at Student Research Day held at MacEwan University in Edmonton, Alberta.
Keywords: personas; UX design